Reflections Upon a Stage in the Maturation of AMJ and the AOM - Mahoney, Thomas A. (Academy of Management Journal, 1997)
A personal narrative is presented that explores the author?s experience as editor of the ?Academy of Management Journal,? during the years 1982-1984.